1989
DOI: 10.1017/s0022215100156725
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal laryngectomy with myomucosal shunt

Abstract: This is a modified subtotal laryngectomy. On the tumour-free side of the larynx, some posterior structures, with their neurovascular supply are preserved. The endolaryngeal mucosa is tubed in continuity with the trachea below and projects into the pharynx above. Thus a myomucosal shunt is formed. Air is directed into it by finger occlusion of the tracheal stoma.The voice production is highly satisfactory. Aspiration is prevented by constriction of the thyroarytenoid muscle which provides a valved upper end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…The second potential criticism of the NTL procedure is the technical challenge associated with any new technique. In fact, a review of the literature revealed only three other authors who reported experience with the NTL, all at European institutions 6‐8 . In this report, we describe three minor modifications of the NTL procedure.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The second potential criticism of the NTL procedure is the technical challenge associated with any new technique. In fact, a review of the literature revealed only three other authors who reported experience with the NTL, all at European institutions 6‐8 . In this report, we describe three minor modifications of the NTL procedure.…”
Section: Discussionmentioning
confidence: 85%
“…The NTL is now an accepted alternative to TL for patients with glottic cancer, as well as supraglottic, base of tongue, and hypopharyngeal cancers 3 . Although quite good oncologic 4 and physiologic 5 results have been reported, the use of this technique has thus far been reported subsequently in only small series from the non‐American literature 6‐8 . One reason may be that at approximately the same time that the NTL was introduced, Singer and Blom 9 began popularizing the technique of tracheoesophageal puncture (TEP), 10 which has had a high success rate due in large part to newly developed silicone prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of successful speech outcomes ranges from 74 to 100 per cent. 4,8,9,11,12,[14][15][16][17][18]20,21,[23][24][25][26][27][28][29][30][31][32][33][34] The results of various studies are summarised in Table II. In the previously published series, we analysed the speech outcomes of 150 patients with carcinoma of the larynx and pyriform fossa who underwent neartotal laryngectomy at our institution. Intelligible speech was acquired by 90 per cent of these patients.…”
Section: Presence Of Speechmentioning
confidence: 99%
“…Near-total laryngectomy has not gained widespread approval, and few series have been published in the Englishlanguage literature. [9][10][11][12][13][14] The perception of the operative technique as complicated by many surgeons and the widespread and convenient application of tracheoesophageal puncture procedure are among possible causes for this reluctance to perform near-total laryngectomy.…”
mentioning
confidence: 99%